Immunoglobulin A-nephropathy: modern view of the problem and treatment options - I. T. Murkamilov; I. S. Sabirov; V. V. Fomin; Zh. A. Murkamilova (Лечащий Врач, 2021)
The presented review discusses the mechanisms of development, the issues of diagnosis and the possibility of therapy for IgAnephropathy. IgA-nephropathy is an immunocomplex lesion of the glomeruli, characterized by the predominant deposition of immunoglobulin A in the mesangia. IgA-nephropathy meets all the criteria of an immune-inflammatory disease and is a common type of chronic glomerulonephritis in all countries of the world. Changes in the molecular structure of IgA, disturbances in the processes of its glycosylation and polymerization, as well as the deposition of polymeric IgAl in the glomerular mesangium underlie the pathogenesis of the disease. There are primary, secondary, sporadic and familial forms of IgA-nephropathy. According to the clinical course, the classical, asymptomatic and atypical variants of the course of IgA-nephropathy are distinguished. Clinical manifestations of IgA-nephropathy consist of macro- or microhematuria, proteinuria and arterial hypertension. The final diagnosis is made with nephrobiopsy. Differential diagnosis is made between urolithiasis, renal tumor, secondary nephropathy, Alport syndrome, disease of thin basement membranes. In the treatment of IgA-nephropathy, blockers of the renin-angiotensin-aldosterone system are used; a positive effect of tonsillectomy is possible. Glucocorticoids and cytostatics are recommended for nephrotic proteinuria, rapid disease progression, or signs of renal activity on morphological examination. The prognosis is good, although approximately 40% of patients develop dialysis-dependent end-stage renal disease after 15 to 20 years.